Characterization and genetic diversity of photoperiodic among mutant kenaf (Hibiscus Cannabinus L.) using EST-SSR markers - Md Al-Mamun; Yusop, Mohd Rafii; Oladosu, Yusuff; Misran, Azizah; Berahim, Zulkarami; Ahmad, Zaiton; Arolu, Fatai; Hasan Khan, Md Mahmudul (Taylor and Francis, 2021)
Information on molecular genetic diversity among Hibiscus cannabinus L. lines is crucial for developing a new variety from the existing germplasms based on consumer demand. Based on this premise, the allelic diversity of thirty-one kenaf genotypes were assessed using polymorphic EST-SSR. From the 72 EST-SSR primers tested, 10 showed sharp and clear polymorphic bands ranging from 4 (137 to 225 bp) to 7 (182 to 382 bp) alleles with a mean value of 5.2 per primer. The Polymorphism Information Content (PIC) value ranged from 0.531 to 0.737, with a mean of 0.610, indicating that the genotypes are genetically diverse. Shannon index estimation varied from 0.982 to 1.515, whereas 0.123 to 0.405 was recorded within the groups. Genetic differentiation ranged from 0.67 to 1 alongside the average gene flow (Nm) of 0.024. The AMOVA revealed 76% variation within the population, while the population gain recorded was 24%. UPGMA dendrogram indicated the relationship and categorized the evaluated kenaf mutants into five major groups. This study revealed the existence of significant variation in kenaf mutants based on EST-microsatellites. These results could be used for future breeding programs and conservation of germplasms to enhance Hibiscus cannabinus L. genotypes.